2021
DOI: 10.3389/fonc.2021.722331
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin: A Potential Drug for the Treatment of Malignancies and Inflammatory Diseases

Abstract: Dihydroartemisinin (DHA) has been globally recognized for its efficacy and safety in the clinical treatment of malaria for decades. Recently, it has been found that DHA inhibits malignant tumor growth and regulates immune system function in addition to anti-malaria. In parasites and tumors, DHA causes severe oxidative stress by inducing excessive reactive oxygen species production. DHA also kills tumor cells by inducing programmed cell death, blocking cell cycle and enhancing anti-tumor immunity. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 139 publications
1
32
0
Order By: Relevance
“…Similarly, Li et al demonstrated that DHA inhibited myeloidderived suppressor cells senescence to ameliorate the development of systemic lupus [48]. Moreover, it is well documented that DHA significantly inhibits expression of proinflammatory cytokines and alleviates inflammatory diseases, including inflammatory bowel disease, rheumatoid arthritis, lupus nephritis, and allergic asthma [49]. Correspondingly, we demonstrated that DHA exerted anti-inflammation effects and improved SASP through inhibiting the expression of MMPs and proinflammatory cytokines.…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, Li et al demonstrated that DHA inhibited myeloidderived suppressor cells senescence to ameliorate the development of systemic lupus [48]. Moreover, it is well documented that DHA significantly inhibits expression of proinflammatory cytokines and alleviates inflammatory diseases, including inflammatory bowel disease, rheumatoid arthritis, lupus nephritis, and allergic asthma [49]. Correspondingly, we demonstrated that DHA exerted anti-inflammation effects and improved SASP through inhibiting the expression of MMPs and proinflammatory cytokines.…”
Section: Discussionsupporting
confidence: 74%
“…DHA is well known for its safety and efficacy in treatment malaria by disrupting mitochondrial function and inducing oxidative stress. 28,29 Recently, DHA has received increasing attention because it exerts significant antitumor activity in various malignant tumors and low toxicity to normal cells at appropriate doses 30 ; thus, it can be used to enhance the anticancer effects of a variety of clinical drugs and was demonstrated to be an effective antitumor drug. 31,32 DHA can exert its antitumor activity in CC, 10,33 but the molecular mechanism is still obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were seeded into 96-well plates at a density of 5 × 10 3 per well for RKO cells and 8 × 10 3 per well for HCT116 cells and cultured until the cells completely adhered. For cell cytotoxicity assay, cells were exposed to DHA at different concentrations (10,20,30, 40, 50 μM) and oxaliplatin at different concentrations (1, 2, 5, 10 μM) for 24−72 h, which according to different experiment. Finally, CCK-8 solution (90 μl completely DMEM with 10 μl CCK-8) was added to the cells.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…In addition to antimalarial activity, artemisinin and its derivatives have also been discovered as potential candidates for anti-infammatory and antitumor activities [13][14][15][16][17][18][19]. Reports show that artesunate is a potent inhibitor of many cancer cell lines and efectively prevents metastasis of tumor cells [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%